Hedging in Academic Discourse: Native English Speakers vs. Czech and Slovak Writers - Věra Sládková (Littera Scripta, 2017)
The pervasiveness of hedging in Anglo-American academic discourse is determined by the dialogic nature of research articles, which allow scientists to tentatively present their findings and ask colleagues with modesty and deference for their acceptance. Hedging devices allow researchers to express the lack of complete commitment to the truth of the proposition, or unwillingness to state a claim categorically. The comparison of frequencies and functions of hedging devices in individual sections of native English speakers’ research articles to those written by Czech and Slovak authors revealed considerable differences in the article structure and the overall aims of individual sections, which is probably caused by the different socio-pragmatic context. Czech and Slovak writers underestimate the use of mainly reader-motivated hedges in all parts of the articles, do not appear to admit the constraints of the research, and seldom show awareness of the relatively minor value of their findings.